Lew i smok. Zderzenie dwóch koncepcji stosunków międzynarodowych na przykładzie brytyjskiej misji lorda Macartneya do Chin w latach 1793-1794 - Wasilewski, Paweł (Studia Azjatystyczne, 2016)
This paper discusses different conceptions of international relations (Westphalian sovereignty and China’s model based on a tributary system and the central place of the imperial court in Beijing) in the context of the British expedition to China in 1793-1794. There is perhaps no more striking case of a clash between Britain and China. This confrontation was a part of the colonial period. The British mission undertook the task of commencing trade cooperation with the Chinese and establishing a permanent embassy in Beijing. The embassy was ultimately not successful. After the conclusion of the embassy, Qianlong sent a letter to King George III, explaining in greater depth the reasons of his refusal to grant the requests of the embassy. This paper shows that the only way to success was mutual understanding. The failure to obtain trade concessions was caused not only by Macartney’s refusal to kowtow in the presence of the Qianlong Emperor, as is commonly believed. It was a result of competing world views that were mutually incomprehensible and incompatible. China had a totally different perspective on their role in the world. As ruler of the “Middle Kingdom”, the Emperor of China received a Mandate from Heaven, and was nominally ruler of the entire world. China had a privileged status in the world and others could be beneficiaries of Chinese culture only on condition that they admitted this particular role. A lack of understanding of the cultural context of Chinese international relations caused the failure of the embassy.